Cardiomyocyte-specific disruption of the circadian BMAL1–REV-ERBα/β regulatory network impacts distinct miRNA species in the murine heart - Mary N. Latimer; Lamario J. Williams; Gobinath Shanmugan; Bryce J. Carpenter; Mitchell A. Lazar; Pieterjan Dierickx; Martin E. Young (Communications Biology, 2023)
Abstract Circadian disruption increases cardiovascular disease (CVD) risk, through poorly understood mechanisms. Given that small RNA species are critical modulators of cardiac physiology/pathology, we sought to determine the extent to which cardiomyocyte circadian clock (CCC) disruption impacts cardiac small RNA species. Accordingly, we collected hearts from cardiomyocyte-specific Bmal1 knockout (CBK; a model of CCC disruption) and littermate control (CON) mice at multiple times of the day, followed by small RNA-seq. The data reveal 47 differentially expressed miRNAs species in CBK hearts. Subsequent bioinformatic analyses predict that differentially expressed miRNA species in CBK hearts influence processes such as circadian rhythmicity, cellular signaling, and metabolism. Of the induced miRNAs in CBK hearts, 7 are predicted to be targeted by the transcriptional repressors REV-ERBα/β (integral circadian clock components that are directly regulated by BMAL1). Similar to CBK hearts, cardiomyocyte-specific Rev-erbα/β double knockout (CM-RevDKO) mouse hearts exhibit increased let-7c-1-3p, miR-23b-5p, miR-139-3p, miR-5123, and miR-7068-3p levels. Importantly, 19 putative targets of these 5 miRNAs are commonly repressed in CBK and CM-RevDKO heart (of which 16 are targeted by let-7c-1-3p). These observations suggest that disruption of the circadian BMAL1–REV-ERBα/β regulatory network in the heart induces distinct miRNAs, whose mRNA targets impact critical cellular functions.